2005
DOI: 10.7861/clinmedicine.5-3-264
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulonephritis: is it worth worrying about?

Abstract: -Glomerulonephritis (GN) is a group of conditions characterised by inflammation in the filtering units of the kidney which may be 'primary'; secondary to drugs, infections or tumours; or the presenting feature of systemic disease. GN is treatable, causes significant morbidity and mortality, and is a potentially preventable cause of renal failure and cardiovascular risk. It can only be precisely identified and characterised by renal biopsy which is usually undertaken in specialist nephrology centres. The role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Several studies have demonstrated that glomerular disorders are a multifactorial process caused by immune and nonimmune mechanisms that lead to glomerulosclerosis, tubulointerstitial fibrosis, inflammatory infiltration, loss of renal parenchyma, and renal vascular changes [ 5 , 6 ]. Although glomerular disorders can cause significant morbidity and mortality, they are treatable and constitute a preventable cause of renal failure and cardiovascular risk [ 7 ]. Importantly, the early recognition of the disease and the timely institution of appropriate treatment for patients with glomerular disorders should be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that glomerular disorders are a multifactorial process caused by immune and nonimmune mechanisms that lead to glomerulosclerosis, tubulointerstitial fibrosis, inflammatory infiltration, loss of renal parenchyma, and renal vascular changes [ 5 , 6 ]. Although glomerular disorders can cause significant morbidity and mortality, they are treatable and constitute a preventable cause of renal failure and cardiovascular risk [ 7 ]. Importantly, the early recognition of the disease and the timely institution of appropriate treatment for patients with glomerular disorders should be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…GN is a preventable risk factor for renal failure and cardiovascular disease [ 2 ]. The isolated presence of blood and/or protein in the urine, nephrotic (consisting of proteinuria, edema, and hyperlipidemia) or nephritic (consisting of hematuria and hypertension) syndromes, and acute or chronic kidney failure are clinical manifestations of glomerular involvement [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…GN is an important cause of end-stage renal disease (ESRD) and late diagnosis of GN remains a major problem; non-specialists can have a vital role in improving the management of GN by knowing when to suspect it, arranging appropriate investigations and making early referral to a nephrologist. 1 Proteinuria is a cardinal feature of GN and the importance of proteinuria to the generalist is emphasized by the fact that it is now also recognized as an unequivocal independent cardiovascular risk factor. 2 Proteinuria may be asymptomatic, especially at low concentration; when severe it may be associated with nephrotic syndrome, in which the patient's symptoms typically include oedema and lethargy which can be profound.…”
mentioning
confidence: 99%